Exact solutions to the various nonlinear evolution equations - Kaya, Dogan; Inan, Ibrahim E. (Iop Publishing Ltd, 2009)
In this paper, we implemented the exp-function method for the exact solutions of the generalized Fisher's equations, the Burgers-like equation and the Sharma-Tasso-Olver equation. By using this scheme, we found some exact solutions of the above-mentioned equations.
Keywords: Solitary-Wave Solutions; Auto-Backlund Transformation; Homogeneous Balance Method; Burgers-Type Equations; Exp-Function Method; Compound Kdv-Type; Tanh Method; Explicit; Terms